PENGEMBANGAN SOAL TES PILIHAN GANDA KOMPETENSI SISTEM STARTER DAN PENGISIAN PROGRAM KEAHLIAN TEKNIK MEKANIK OTOMOTIF KELAS XII - Widyantoro, Deni; Boenasir, -; Karsono, - (Jurnal Pendidikan Teknik Mesin, 2009)
This research aim to get the problem of tes of double helix of interest of systemof starter and admission filling owning good quality, through problem development ofpursuant to problem analysis qualitative and quantitative. Research method used bydescriptive method, this research there no sampel of because research conductedrepresent the good research population. Problem fulfilling conditions analyse qualitativeas well as after conducted by a quantitative analysis own the level of problem difficultyrange from 0,30 up to 0,70, different energy of bigger problem than 0,30, distraktorselected by 5% from entire competitor tes, and above reliabilitas problem 0,50. Problemconsistence of between tes 1 and tes 2 calculated by using formula of correlation ofproduct moment, if rhitung of bigger than rtabel with the level signifikansi 5% problem isconsistence. Problem of Tes of double helix to be made by a evaluation appliance oughtto be conducted by development of problem tes by analysis of problem item qualitativeand quantitatively before used to measure the achievement of result of learning student.Kata kunci: pengembangan, tes pilihan ganda, sistem starter dan pengisian.